2000
DOI: 10.1034/j.1399-3003.2000.15e18.x
|View full text |Cite
|
Sign up to set email alerts
|

The response of human bone marrow to chronic cigarette smoking

Abstract: Chronic cigarette smoking in humans causes leukocytosis. Animal studies show that chronic smoking shortens the transit time of polymorphonuclear leukocytes (PMNLs) through the bone marrow. The present study examines the response of human bone marrow to chronic cigarette smoking.Three characteristics of peripheral blood PMNLs that indicate active bone marrow release (band cell counts, surface L-selectin expression and myeloperoxidase (MPO) content), were measured in 38 healthy chronic smokers (23 5 pack-yrs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
91
0
10

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(112 citation statements)
references
References 34 publications
(38 reference statements)
10
91
0
10
Order By: Relevance
“…Whereas some investigators have shown that there is increased MPO activity in polymorphonuclear leukocytes in smokers (measured by flow cytometry), others have demonstrated no increased peroxidase activity (quantified by the MPXI, a parameter produced by automated blood counters) in neutrophils of smokers as compared with non-smokers. 32,33 We conclude that current evidence is controversial, and our finding that there was no significant elevation in serum in smokers may reflect the distinction between circulating versus tissue concentrations or may reflect differences in MPO assays.…”
Section: Individual Markersmentioning
confidence: 79%
“…Whereas some investigators have shown that there is increased MPO activity in polymorphonuclear leukocytes in smokers (measured by flow cytometry), others have demonstrated no increased peroxidase activity (quantified by the MPXI, a parameter produced by automated blood counters) in neutrophils of smokers as compared with non-smokers. 32,33 We conclude that current evidence is controversial, and our finding that there was no significant elevation in serum in smokers may reflect the distinction between circulating versus tissue concentrations or may reflect differences in MPO assays.…”
Section: Individual Markersmentioning
confidence: 79%
“…Smoking also causes a chronic, low-grade leukocytosis characterised by increased numbers of immature neutrophils with a pro-inflammatory phenotype which accumulate in the lungs [54]. Migration of circulating neutrophils and monocytes to the lungs is facilitated by smoke-mediated: i) activation of the β2-integrin, CR3, on phagocytes together with upregulated expression of its counterreceptor ,ICAM-1, on vascular endothelium; and ii) increased production of neutrophil/monocyte-attracting chemokines, as well as endothelium-interactive, proadhesive cytokines, by smoke-exposed resident airway and infiltrating cells [55,56].…”
Section: Pro-inflammatory Effects Of Smokingmentioning
confidence: 99%
“…More recently, Di Lorenzo et al (2006) reported an association between Pb exposure and the numbers of circulating neutrophils, with the strongest association being observed in occupationally-exposed workers who smoked [49]. This latter observation is not surprising given the well-recognized association of smoking with: i) neutrophilia [50]; and ii) increased levels of Pb in the blood of smokers as described above. Although the authors speculate that increased numbers of circulating neutrophils may represent a mechanism to compensate for Pb-mediated immune dysfunction, they concede that it is more likely to reflect a neuroendocrine response to toxicity/stress.…”
Section: Leadmentioning
confidence: 72%